The Arabidopsis Mediator Complex Subunits MED16, MED14, and MED2 Regulate Mediator and RNA Polymerase II Recruitment to CBF-Responsive Cold-Regulated Genes . Issue 1 (10th January 2014) - Hemsley, Piers A.; Hurst, Charlotte H.; Kaliyadasa, Ewon; Lamb, Rebecca; Knight, Marc R.; De Cothi, Elizabeth A.; Steele, John F.; Knight, Heather
Abstract : This article demonstrates roles for three subunits of the Plant Mediator complex in recruiting Mediator and RNA polymerase II to specific cold-upregulated genes, facilitating their expression and the subsequent gain of freezing tolerance by the plant. Not all Mediator subunits regulate the same genes, with dark-inducible expression using different subunits than cold-inducible expression. Abstract: The Mediator16 (MED16; formerly termed SENSITIVE TO FREEZING6 [SFR6]) subunit of the plant Mediator transcriptional coactivator complex regulates cold-responsive gene expression in Arabidopsis thaliana, acting downstream of the C-repeat binding factor (CBF) transcription factors to recruit the core Mediator complex to cold-regulated genes. Here, we use loss-of-function mutants to show that RNA polymerase II recruitment to CBF-responsive cold-regulated genes requires MED16, MED2, and MED14 subunits. Transcription of genes known to be regulated via CBFs binding to the C-repeat motif/drought-responsive element promoter motif requires all three Mediator subunits, as does cold acclimation–induced freezing tolerance. In addition, these three subunits are required for low temperature–induced expression of some other, but not all, cold-responsive genes, including genes that are not known targets of CBFs. Genes inducible by darkness also required MED16 but required a different combination of Mediator subunits for their expression than the genes induced by cold. Together, our data illustrate that plants control transcription of specific genes through the action of subsets of Mediator subunits; the specific combination defined by the nature of the stimulus but also by the identity of the gene induced.